Humanitarian Innovation Guide - ELHRA (2018)
The Humanitarian Innovation Guide is a growing online resource to help individuals and organisations define humanitarian problems and succes sfully develop innovative solutions. ABOUT THE GUIDE The humanitarian sector is investing in exciting innovations, but it is not yet produci ng a steady pipeline of well-designed solutions that effectively addre ss problems, evidence their impact, and have the potential to be scale d. As stated in a recent independent evaluation of the Humanitarian In novation Fund (Triple Line, 2017), a review of the innovation ecosyste m in 2015 found significant gaps in resources for innovation, includin g a shortage of guidance on the skills needed to manage successful inn ovation projects. These findings were echoed in the research carried o ut to inform this resource. As part of a grant agreement with the Euro pean Commission to provide financial and technical support to emerging humanitarian innovations, and in line with our strategic aim to devel op the sector’s skills and capabilities in humanitarian innovation, th is resource aims to translate our own learning, along with learning fr om across the sector, into a practical, grounded guide for innovators working in humanitarian contexts. Building on our unique position in t he sector, the Humanitarian Innovation Guide is designed to provide ta rgeted support to individuals and organisations attempting to develop innovative solutions to the challenges facing humanitarian assistance, resulting in a more effective humanitarian response. The Guide is wri tten with two audiences in mind: humanitarian practitioners who are se eking to develop a new approach to their work and want to apply an inn ovation lens to solving problems; and social entrepreneurs from outsid e the sector who have identified an opportunity to engage with the sec tor and need a humanitarian framework to contextualise their innovatio n plans. We also hope that it will be a useful resource for innovation managers who are tasked with supporting innovation in their agencies, labs or networks. As the first step-by-step guide to managing innovat ion in the humanitarian sector, we hope that its continued development will better enable individuals, organisations and the wider sector to : Plan the activities involved in an innovation process and systematis e the management of innovation. Manage a successful innovation project and generate evidence for innovation. Ensure that innovations are dev eloped in an ethical way, with full consideration of risks and respons ibilities.